mitoBKCa is functionally expressed in murine and human breast cancer cells and potentially contributes to metabolic reprogramming - Helmut Bischof; Selina Maier; Piotr Koprowski; Bogusz Kulawiak; Sandra Burgstaller; Joanna Jasińska; Kristian Serafimov; Monika Zochowska; Dominic Gross; Werner Schroth; Lucas Matt; David Arturo Juarez Lopez; et al. (eLife, 2024)
Alterations in the function of K+ channels such as the voltage- and Ca2+-activated K+ channel of large conductance (BKCa) reportedly promote breast cancer (BC) development and progression. Underlying molecular mechanisms remain, however, elusive. Here, we provide electrophysiological evidence for a BKCa splice variant localized to the inner mitochondrial membrane of murine and human BC cells (mitoBKCa). Through a combination of genetic knockdown and knockout along with a cell permeable BKCa channel blocker, we show that mitoBKCa modulates overall cellular and mitochondrial energy production, and mediates the metabolic rewiring referred to as the ‘Warburg effect’, thereby promoting BC cell proliferation in the presence and absence of oxygen. Additionally, we detect mitoBKCa and BKCa transcripts in low or high abundance, respectively, in clinical BC specimens. Together, our results emphasize, that targeting mitoBKCa could represent a treatment strategy for selected BC patients in future.